Histoire de la famille et histoire des mentalités - Flandrin, Jean-Louis (Historical Papers / Communications historiques, 1983)
AsbtractThis year's Distinguished Historian, Professor Jean-Louis Flandrin of the Université de Paris 8 - Vincennes and the Ecole des Hautes Études en Sciences Sociales, surveyed the state of his major field of interest, the inter-relationship between family and psychological history. These are relatively new fields, and the links between them are comparatively unexplored as a result. Yet, in spite of some false starts, much has been accomplished, the work-in-progress contains great promise and the possible avenues for future work are almost limitless. Much will be achieved if the crossfertilization of the various disciplines continues.The author then reviews the sub-fields of family history, and cites those works, both published and unpublished, which appear to offer fresh insights and/or research approaches. Problems and weaknesses are also considered. For example, while Georges Duby's book, Le chevalier, la femme et le prêtre is highly praised as a pathfinding study which should be the inspiration for much future work in the area of the study of the evolution of Christian marriage, Professor Flandrin outlines his reservations regarding certain of Duby's theses. Similarly, the work of Edward Shorter and Elizabeth Bandinter receives more than passing criticism. Professor Flandrin devotes the greatest amount of comment to the topic of the quality and nature of interfamily relations over time - a topic which, he concludes, has roused much sterile and unproductive debate but which is richly documented in the sources and ought to be the object of considerable research in the future. Other topics of comment includea) the size and structure of the domestic unitb) the nature of family tiesc) the intermarriage of family membersd) the various motivations for marriage over timee) the evolution of the notion of a Christian marriagef) the mores surrounding sexual relations within marriageg) feelings between and among family membersThe author concludes with a warning of the need to be sensitive to the variety of interpretation possible in assessing historical behaviour which may vary widely from our own contemporary cultural norms.